Quality, reliability, security and robustness in heterogeneous networks : 12th International Conference, QShine 2016, Seoul, Korea, July 7-8, 2016, Proceedings /: 12th International Conference, QShine 2016, Seoul, Korea, July 7-8, 2016, Proceedings. (2017) - Unknown
No abstract available